The functioning of the Crimean Tatar language in the authorities and administration of the Crimean Autonomous Soviet Socialist Republic in the context of the policy of indigenization (20–30s of the XX century) - Grigorii Kondratjuk (Крымское историческое обозрение)
The article analyzes the main directions of the indigenization policy. The use of the Crimean Tatar language in the work of government and management bodies has been studied. The Bolsheviks’ hopes for a proletarian revolution in Western Europe did not come true, and the vector of foreign policy hopes became the East (Turkey and Iran). The creation of the Crimean autonomy was supposed to demonstrate that the needs of the Turkic peoples could be resolved in the Soviet Union, but not in the principles of Kemalism, but in the Communist Party. In this task, the Crimean Tatars were to act as conductors of Bolshevik ideas. This circumstance formed the basis of the specificity of the policy of indigenization on the peninsula, which was reflected in the term “Tatarization”. A special direction of national policy has become the indigenization of government and administrative institutions, and an important political aspect is the use of the Crimean Tatar language in the area of state building. The author proposes a periodization of the implementation of national policy, which is divided into four stages. 1) 1917–1923 – search for conceptual principles for the implementation of ethnopolicy; 2) 1923–1928 – official proclamation of indigenization and an attack on national communists in the Turkic republics; 3) 1928–1934 – administrative stage; 4) 1934–1938 – formation of national collective farms and the Crimean Tatar proletariat. Research materials: The theoretical works of the leaders of the People’s Commissariat of Nationalities of the RSFSR were used, as well as unpublished documents from the State Archive of the Republic of Crimea. Results and novelty of the research:The article analyzes the relationship between various aspects of the indigenization policy in the Crimean Autonomous Soviet Socialist Republic and the change in the legal status of the Crimean Tatar language.